The Effect of Multiple Role Conflict and Work Stress on the Performance of Female Nurses at Permata Bunda General Hospital, Medan - Rani Duita Pohan; Ritha Z. Tarigan (Journal of Economics and Business (JECOMBI), 2022)
This research was conducted based on the conditions of organizational performance at the General Hospital of the General Hospital which showed that the organizational performance targets set by the Ministry of Health were not achieved, this is in line with the individual employee performance indicators shown from the low employee attendance data. The purpose of this study was to determine the effect of multiple role conflict, job stress, and the effect of multiple role conflict and work stress simultaneously on performance. The results of this study provide input to female employees at Permata Bunda General Hospital Medan to be able to further improve their performance as professional employees, in order to support the performance of the Permata Bunda General Hospital Medan.